Produção e uso dos manuais escolares no trabalho pedagógico das professoras no ciclo de formação humana: a experiência do Colégio Iraci Salete Strozak - Castelari, Jucelia (2021)
This research aimed to understand the relations between the school form and the pedagogical work of female teachers with textbooks in the context of the Landless Rural Workers Movement (MST), based on the Human Formation Cycle. To this end, the historical panorama of the School Textbook Policy in Brazil from 1937 to the present day was investigated. In addition, the educational principles of the Movement are presented, which proposes an educational project as an alternative for the transformation of the school system and which records its historical trajectory in the textbooks produced by the people in struggle. In this respect, the research discusses the Cycles of Human Formation, the Study Complexes, and the Itinerant Schools. Methodologically, this is qualitative research, based on bibliographic research, with a critical theoretical basis, listing categories such as textbooks (MELO, 2012; FILGUEIRAS, 2011, 2015; GHERKE, 2014; CASSIANO, 2016); the school form (ENGUITA, 1989; MANACORDA, 1997; VICENTE; LIHENE; THIN, 2001; FREITAS, 2003; CALDART, 2005; MESZÀROS, 2005); and the Human Formation Cycles (TEIXEIRA, 2008; MAINARDES, 2009; MST, 2013; SAPELLI; LEITE; BANHIUK, 2017). In addition to the bibliographical research, data were generated from interviews with teachers who work at the State College of the Field Iraci Salete Strozak, observation, and field diary records. The analyses focus on the teachers' work in the Human Formation Cycle with the textbooks, which were categorized into: (i) state textbooks; (ii) private textbooks; (iii) resistance textbooks; and (iv) the textbooks of the school subjects. With results, it wasobserved a high adherence of female teachers in the pedagogical work with the State textbooks and lower adherence to the other textbooks. It was concluded that these serialized and disciplinaries textbooks are bordering the school form in the relationship with their uses and with the uses of the other textbooks. However, tests of transposition of the school form were observed through the use of the set of textbooks in the school library collection and the production of textbooks in the pedagogical work of the teachers, in a way that made itpossible to exercise elements of the organization by Human Formation Cycles, as well as to disseminate meaningful content to the peasants. It is necessary to change the school form by building new relationships between the subjects and the textbooks, breaking the centrality of the teachers' pedagogical work with a single textbook. Moreover, the educating state must expand the ways of operationalizing the policy for textbooks to meet the educational diversity of the country, enabling an expansion in the mode of use and production of textbooks, including a greater approximation of the manuals of resistance subjects with the methodological needs of schools.